2012
DOI: 10.1185/03007995.2012.728131
|View full text |Cite
|
Sign up to set email alerts
|

Publication misconduct and plagiarism retractions: a systematic, retrospective study

Abstract: This is the first study to demonstrate that publications retracted for plagiarism are significantly associated with first authors affiliated with lower-income countries. These findings have implications for developing appropriate evidence-based strategies and allocation of resources to help mitigate plagiarism misconduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 16 publications
1
63
0
3
Order By: Relevance
“…Other studies (using broader databases such as the PubMed index) 5,7,8 have also identified greater incidence of plagiarism among lower-income countries. However, for the present study, it was decided to use an indicator of scientific output as an alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies (using broader databases such as the PubMed index) 5,7,8 have also identified greater incidence of plagiarism among lower-income countries. However, for the present study, it was decided to use an indicator of scientific output as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] More recently, the association between retractions and scientometric factors such as research field, country and other characteristics of authors and journals has become a matter of interest and debate, with a view towards development of strategies for preventing misconduct. 3,5,7,8 For example, if retractions were mostly due to plagiarism, it would be important to focus on procedures such as the use of automatic detection software and journal guidelines for handling plagiarism cases. 9,10 On the other hand, for data fraud, more specific monitoring measures (for instance, introduction of data repositories, random audits and mandatory data sharing in an institution) would be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, significant differences in the frequency of these faults is reported if the authors come from low-income countries and do not speak English as their native language, but there is no information about such a state of affairs from developing countries in Latin America 1 . Although not reported in the study 1 , cases of retraction due to misconduct and plagiarism occur in articles published from Latin American countries [2][3][4] .…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 99%
“…In this study, significant differences in the frequency of these faults is reported if the authors come from low-income countries and do not speak English as their native language, but there is no information about such a state of affairs from developing countries in Latin America 1 . Although not reported in the study 1 , cases of retraction due to misconduct and plagiarism occur in articles published from Latin American countries [2][3][4] . We have performed a literature search using the special queries function 'Retracted Publications' and 'Retraction of Publication' on MEDLINE (search filters: human and animal studies; English; from 1 January 1966 to 18 February 2008) and, additionally, looked for full original publication and retraction notice available, indicating that the publication had been retracted for reason of misconduct.…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 99%
See 1 more Smart Citation